WORLD BANK ASSISTANCE IN ADDRESSING WATER AND SANITATION PROBLEMS IN RIAU THROUGH THE COMMUNITY-BASED DRINKING WATER AND SANITATION PROGRAM (PAMSIMAS III) - Karotriyana Br. Simbolon; Mhd Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The clean water and sanitation crisis is an issue that is still the focus of the international community, because it can affect national and global activities. The problem of clean water and sanitation is alsostill a big problem that continues to be faced by Indonesia. Limited funds to increase the development of access to clean water and sanitation facilities that are evenly distributed is the reason Indonesia needs assistance from outside parties to help overcome these problems. This research will describe how the World Bank as an international financial organization helps address water and sanitation problems in Indonesia through the PAMSIMAS III program. This study uses descriptive qualitative method and data collection techniques for documentary studies and literature studies. In analyzing this topic, researcher use the perspective of institutional liberalism with the level of international system analysis and foreign aid theory in the form of grants and loans. This research shows that the World Bank's financial assistance in the PAMSIMAS III program is considered effective in increasing access to clean water services and improving healty sanitation facilities in Indonesia, specially in Riau Province. This can be seen from the increasing percentage of households that have access to clean water services and the increasing number percentage of households that have access to sanitation. Keywords: Foreign Aid, World Bank, Riau, Clean Water and Sanitation, PAMSIMAS III